Lay attitudes and misconceptions and their implications for the control of brucellosis in an agro-pastoral community in Kilombero district, Tanzania. - Caroline M Mburu; Salome A Bukachi; Kathrin H Tokpa; Gilbert Fokou; Khamati Shilabukha; Mangi Ezekiel; Bassirou Bonfoh; Rudovick Kazwala; Katharina Kreppel (Public Library of Science (PLoS), 2021)
Brucellosis is a priority zoonotic disease in Tanzania that causes ill-health in people and affects livestock productivity. Inadequate awareness and behavior risking transmission can impede control efforts. We conducted a cross-sectional survey of 333 livestock owners in three villages in the Kilombero district, Tanzania, to understand their awareness, knowledge and behavior associated with brucellosis. Six Focus Group Discussions (FGDs), two in each village, were conducted, as well as an additional FGD with male herders from one of the villages. Factors associated with knowledge on brucellosis, food consumption and animal husbandry behavior risking transmission of this disease, were identified using generalized linear models. Predictors for knowledge of brucellosis were being male and having a higher educational level, while age was positively associated with a higher level of knowledge. Faith and ethnicity were associated with the performance of practices risking transmission. Following traditional religion and belonging to the Wamaasai ethnicity significantly increased the odds of carrying out these practices. Qualitative analysis gave insight into risk practices and reasoning. Of the 333 respondents, 29% reported that they had experienced abortions in their herds, 14% witnessed retained placentas, and 8% had seen still-births in their cattle within the previous year. However, survey results also showed that only 7.2% of participants had heard about brucellosis as a disease in livestock. Of those who had heard about brucellosis in livestock, 91% associated abortions with it and 71% knew that humans can get infected through raw milk consumption. People overwhelmingly attributed symptoms and transmission of brucellosis in livestock to infection with trypanosomiasis and to supernatural reasons instead. In the community, consumption of raw milk was valued and handling of aborted material was not considered a risk for infection. This agro-pastoralist community holds on to long-held beliefs and practices and lacks understanding of the biomedical concept of brucellosis. Transmission routes and symptoms of brucellosis in humans and livestock are completely unknown. The disparity between risk perception and actual transmission risk related to animal handling and consumption of animal products presents a challenge for disease awareness communication. This study recommends focused community engagement and sensitization to address the limited awareness and misconceptions among agro-pastoralists.